Research progress on the hydrogen permeation behavior of the nuclear waste container–A mini review - Zhang, Qichao; Jiang, Yishan; Zhang, Binbin; Duan, Jizhou; Zhao, Xin; Chen, Juna (Frontiers in Materials, 2022)
A large amount of nuclear waste produced in the process of nuclear energy utilization has always been a key problem to be solved urgently for nuclear safety. At present, “deep geological disposal” is a feasible method and generally accepted by many countries. It is a “multi barrier system” composed of artificial barrier including solidified waste body, outer packaging material, buffer backfill material and natural barrier including surrounding rock. During deep geological disposal, a near field environment where the corrosion of container could happen is formed with the continuous groundwater infiltration and the release of much heat energy in the process of nuclear waste decay and fission. At the same time, the environment will become a long-term reduction place because of the gradual consumption of initial retained oxygen. Hydrogen evolution reaction is dominant, so unpredictable hydrogen embrittlement of the container materials could happen due to hydrogen absorption and penetration. This paper summarizes the possibility of hydrogen embrittlement of carbon steel, titanium and their alloys from three aspects: hydrogen solubility, diffusion coefficient and hydrogen embrittlement, which provides theoretical basis for predicting container life in a large time scale.